Exploring the Dimensions of Movement-Specific Reinvestment From Personal Characteristics Perspectives - Kawabata, Masato; Imanaka, Kuniyasu (Frontiers in Psychology, 2021)
The purposes of the present study were threefold: to examine a) if the movement-specific reinvestment responses should be represented as two dimensional constructs, b) whether dichotomization of the movement-specific reinvestment responses are appropriate, and c) how the two dimensions are associated with relevant psychological concepts. To conduct a comparative examination of the MSRS structure in two Asian samples, participants were 236 Japanese university students (136 men, 100 women; Mage = 18.0, SD = 1.6) and 328 Singaporeans (167 men, 161 women; Mage = 21.8, SD = 1.8). After examining the factor structure of the movement-specific reinvestment responses for the first purpose, latent class factor analysis was conducted for both samples for the second purpose. For the third purpose, correlation analysis and mediation analysis were conducted for a part of the Singaporean sample. Through a series of latent class factor analysis, four and three classes were identiﬁed for the Japanese and Singaporean samples, respectively. For both samples, the patterns of the item-average scores for the two movement-specific reinvestment dimensions were parallel among the classes. Conscious Motor Processing was positively associated with mental toughness, intrinsic regulation, integrated regulation, mastery-approach and task goal orientations, and dispositional flow, whereas Movement Self-Consciousness was positively related with stress, and mastery-avoidance goal orientation. The findings of the study supported a) the two-dimensional representation of the movement-specific reinvestment responses, but did not fully support b) the practice of dichotomization of the movement-specific reinvestment responses, and indicated that c) at the trait level, Conscious Motor Processing and Movement Self-Consciousness were associated with positive and negative psychological constructs, respectively.